Melaka Sustainability Outlook Diagnostic : Supporting Report 2 - Integrating Environmental Plans - Global Platform for Sustainable Cities (World Bank, Washington, DC, 2019)
Rapid urbanization and overconsumption can threaten the natural environment, resource efficiency and resilience of a region, which are essential components of urban sustainability. Human effects which cause environmental degradation include poor sanitation and waste disposal, overconsumption of water resources, and motorized vehicular and industrial activities contributing to increased levels of greenhouse gas (GHG) emissions. Malaysia has made ambitious commitments to reduce its GHG emissions intensity of GDP by forty-five percent by 2030 relative to the emissions intensity of gross domestic product (GDP) in 2005. Melaka’s rapid urbanization rate and population growth are already placing pressures on the environment. Melaka State has been ambitious in its efforts in attracting international expertise from numerous multilateral development banks and aid organizations. There is, however, the potential for key issues around coordination of funding and implementation to be overlooked in the rapid race to meet the city’s environmental objectives. This report offers a detailed snapshot of the current environment and resource efficiency dynamics of Melaka in comparison with similar regions in Malaysia and abroad, and with analysis of performance in the areas of water, waste, energy and resilience. The report concludes by discussing the emerging risks and challenges that Melaka faces and outlines key recommendations for the state.